Building a Future Research Agenda for Reducing Meat Consumption: A Review on Social Norms, Food, and Drink - Cristina M. Ostermann; Márcia Dutra de Barcellos (Innovar: Revista de Ciencias Administrativas y Sociales)
Scientific studies have indicated the need for sustainable diets that reduce or exclude meat consumption to address the climate crisis. However, new dietary patterns require challenging changes in consumer behavior, and social norms can be a means to achieve this. This study aims to provide a future research agenda on meat consumption and social norms based on an overview of quantitative empirical research related to social norms and food and beverage consumption behavior. We seek to fill a gap in the literature by relating a consolidated and widely used theory in behavioral interventions to a topic of current academic and social attention. From a systematic review of peer-reviewed articles, we identified interpretable patterns, including theories, methodologies, geographic focus, year of publication, samples, and demographic variables. Our results highlighted investigations conducted in the United States, using the Focus Theory of Normative Conduct as a theoretical lens and involving undergraduate students. We propose six opportunities for further research considering three dimensions: theoretical, methodological, and contextual. The proposals of this study for future research provide a foundation for researchers, reinforcing the academic, theoretical, and social contributions. Our research has limitations inherent to systematic reviews, with possible variations in search results from other databases, different filtering processes adopted, and the inclusion of books and gray literature.